Educational Games and Ice Breaking in Scienci Learning for student of Madrasah Ibtidaiyah/Elementary Schools - Nurmala; Ifrianti, Syofnidah (Universitas Indo Global Mandiri Palembang, 2024)
Objective: Problems frequently observed in educational activities among students of Madrasah Ibtidaiyah or Elementary Schools, particularly in science learning, include low motivation, limited concentration, exhaustion, and boredom when participating in classroom learning processes. Design/Methods/Approach: The method employed in this study is a qualitative approach. The research approach utilized is a library research method involving in-depth observation and analysis of scientific article sources centered on literature review Findings: Efforts that can be implemented to address these challenges involve educators needing to introduce strategies capable of enhancing focus capacity and student motivation within the classroom environment, such as utilizing educational games and ice-breaking activities. This academic work aims to examine the application of educational games and ice-breaking in science learning activities for MI/SD students. Originality/Value: This academic work aims to examine the application of educational games and ice-breaking in science learning activities for MI/SD students. Practical/Policy implication: Based on these findings, it can be concluded that the learning process through educational games and ice-breaking activities in science learning for Madrasah Ibtidaiyah or Elementary School students is highly appropriate for implementation in classroom teaching activities because educational games and ice-breaking are capable of optimizing motivation, focus, enthusiasm, interest, concentration, and learning outcomes of students during the science learning process in the classroom.